Financing public expenditures through progressive taxation: effects on growth, welfare and inequality - Ünsal, Alper. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Theoretical and empirical studies have revealed that there is a positive impact of public investments, i.e. infrastructure investments, on economic growth. Noting that the growth literature containing productive public capital often neglects distributional effects and the relevant studies rely on financing methods using flat taxation, the implications of having a progressive tax schedule on economic growth and distributional measures are explored in this study. More specifically, an endogenous growth model is used in which public investment is a direct factor in both production and utility functions while labor-elastic agents are taxed progressively according to their relative capital income and labor income levels. After forming the theoretical model, numerical analyses are also conducted to find the effects of increases in public expenditures on both economy-wide parameters, i.e. GDP growth rate, and on income, wealth and welfare dispersions. This study shows that, without harming economic growth, it is possible to alleviate inequalities in an economy through increases in public expenditure financed by progressive taxes. Among the discussed tax methods, most influential one on all dimensions is found to be capital income taxes. Its progressivity level has to be assigned to be lower than a threshold level above which it begins to harm economic growth.
Keywords: Public investments.; Economic development.